Hepatitis-Induced Hemolysis in Pediatrics: A Rare Case Report - Dr. Amal Adnan Laylani (Zien Journals, 2023)
This article presents a case study of a 6-year-old boy diagnosed with acute Hepatitis A virus (HAV) infection compounded by glucose-6-phosphate dehydrogenase (G6PD) deficiency. The patient exhibited a constellation of symptoms, including low-grade fever, upper abdominal pain, fatigue, and anorexia, over an 8 to 10-day period. Notably, jaundice, dark-colored urine, and hepatomegaly were prominent clinical features. Laboratory investigations revealed severe intravascular hemolysis, evidenced by a decline in hemoglobin, elevated reticulocytes, and unconjugated hyperbilirubinemia. The diagnosis of HAV hepatitis was confirmed through positive IgM anti-hepatitis A virus. Over the subsequent two weeks, the patient experienced peak levels of serum bilirubin, AST, and ALT. Conservative management focused on avoiding hepatotoxic drugs, ensuring adequate urine output, and monitoring metabolic parameters. Gradual improvement was observed over the subsequent month, with a significant reduction in bilirubin levels, restoration of hemoglobin, and a decline in liver enzymes. The patient was discharged for outpatient follow-up, and four weeks post-onset, G6PD levels approached normal, emphasizing the importance of comprehensive care in such complex cases. This case underscores the intricate interplay between viral hepatitis and G6PD deficiency, contributing valuable insights into the clinical presentation and management of severe hemolysis in this specific population
Keywords: Hepatitis; hemolysis; Children; Hemoglobin